2008
DOI: 10.1080/10715760701790671
|View full text |Cite
|
Sign up to set email alerts
|

Thiols oxidation and covalent binding of BSA by cyclolignanic quinones are enhanced by the magnesium cation

Abstract: A novel cyclolignanic quinone, 7-acetyl-3′,4′-didemethoxy-3′,4′-dioxopodophyllotoxin (CLQ), inhibits topoisomerase II (TOPO II) activity. The extent of this inhibition was greater than that produced by the etoposide quinone (EQ) or etoposide. Glutathione (GSH) reduces EQ and CLQ to their corresponding semiquinones under anaerobic conditions. The latter were detected by EPR spectroscopy in the presence of MgCl 2 but not in its absence. Semiquinone EPR spectra change with quinone/GSH mol ratio, suggesting covale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Alegria et al . () reported that the above‐maintained adducts were also identified for BSA in presence of cyclolignanic quinones. Furthermore, the covalent binding of orthoquinones to BSA is mediated by both thiol groups and amino or imino groups.…”
Section: Resultsmentioning
confidence: 88%
“…Alegria et al . () reported that the above‐maintained adducts were also identified for BSA in presence of cyclolignanic quinones. Furthermore, the covalent binding of orthoquinones to BSA is mediated by both thiol groups and amino or imino groups.…”
Section: Resultsmentioning
confidence: 88%
“…In wine production, the addition of glutathione reduces the browning of wine caused by oxidation of phenols by forming thiol-quinone adducts, where especially, ortho-phenolic structures as present in (+)-catechin or (À)-epicatechin are highly susceptible to adduct formation with nucleophile thiols (Singleton & Cilliers, 1995). The adduct has been identified for several proteins including BSA, a-lactalbumin, and lysosome (Alegria et al, 2008;Prigent, Voragen, Visser, van Koningsveld, & Gruppen, 2007). A similar reaction could be important for beef with plant phenols added as antioxidants, and such reactions are currently studied.…”
Section: Resultsmentioning
confidence: 97%
“…Addition of glutathione reduces the browning of wine caused by oxidation of phenols by forming thiol‐quinone adducts 95, and the adduct has been identified for several proteins e.g . BSA 96. A similar reaction could be important for muscle foods with plant phenols added as anti‐oxidants, and such reactions are currently being studied.…”
Section: Controlling Protein Oxidation In Muscle Foods Anti‐oxidanmentioning
confidence: 99%